Artificial Intelligence and Computational Dynamics for Biomedical Research (Intelligent Biomedical Data Analysis, 2022)
This work presents the latest development in the field of computational intelligence to advance Big Data and Cloud Computing concerning applications in medical diagnosis. As forum for academia and professionals it covers state-of-the-art research challenges and issues in the digital information & knowledge management and the concerns along with the solutions adopted in these fields.